2018
DOI: 10.1007/s12272-018-1024-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the size distributions and immunogenicity of human papillomavirus type 16 L1 virus-like particles produced in insect and yeast cells

Abstract: Insect and yeast cells are considered the expression systems of choice for producing virus-like particles (VLPs), and numerous types of VLPs have been produced in these systems. However, previous studies were restricted to identifying the characteristics of individual VLP preparations. No direct comparison of the structures and immunogenic properties of insect and yeast-derived VLPs has so far been made. In the present study, the size distribution and immunogenic properties of human papillomavirus type 16 (HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…Their different immunogenicity and efficacy may be attributed to the different expression systems. Consistent with our speculation, a study in mice showed that HPV16 L1 VLPs produced in insect cells induced much higher neutralizing antibody titers than those produced in yeast in the absence of adjuvant (Kim et al, 2018). These data suggested that insect cells, a higher eukaryotic expression system, may be more conducive to generating highly immunogenic VLPs.…”
Section: Introductionsupporting
confidence: 88%
“…Their different immunogenicity and efficacy may be attributed to the different expression systems. Consistent with our speculation, a study in mice showed that HPV16 L1 VLPs produced in insect cells induced much higher neutralizing antibody titers than those produced in yeast in the absence of adjuvant (Kim et al, 2018). These data suggested that insect cells, a higher eukaryotic expression system, may be more conducive to generating highly immunogenic VLPs.…”
Section: Introductionsupporting
confidence: 88%
“…The particle size and distribution of VLPs are correlated with their immunogenicity. The closer to the real virus particle (<100 nm), the more symmetrical the VLP icosahedron and the stronger its immunogenicity, 21 as confirmed by our clinical phase III research results (results are not shown). Therefore, according to the change of particle size, at least 0.25% PH, 0.5% PH, 0.1% PE, 0.5% PE, 0.15% CR, 0.5% BA, 1.0% BA, 0.10% MP, and 0.14% MP can be used as preservatives for the HPV-2 vaccine.…”
Section: Resultssupporting
confidence: 60%
“…Previous studies have shown that expressing the full-length PCV3 cap gene and NLS domains presenting within the N-terminal arginine rich motif (ARM) may cause misfolding of the protein and induce formation of circular virus complexes of 10-12 nm (Sarker et al 2016). Other groups have published that, different sizes of VLPs appear in different expression systems (Bucarey et al 2009;Kim et al 2018a;Wu et al 2016), a number of factors including storage conditions (ion-strength, pH and etc.) as well as the process design also influence the characteristics of VLPs (Effio and Hubbuch 2015;Fernandes et al 2013;Kim and Kim 2017b).…”
Section: Discussionmentioning
confidence: 99%